2017
DOI: 10.1177/2192568217743505
|View full text |Cite
|
Sign up to set email alerts
|

The Effectiveness of Bioskills Training for Simulated Lumbar Pedicle Screw Placement

Abstract: Study Design:Prospective randomized study.Objectives:To define the impact of an inexpensive, user-friendly, and reproducible lumbar pedicle screw instrumentation bioskills training module and evaluation protocol.Methods:Participants were randomized to control (n = 9) or intervention (n = 10) groups controlling for level of experience (medical students, junior resident, or senior resident). The intervention group underwent a 20-minute bioskills training module while the control group spent the same time with se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…Multiple studies have demonstrated that learning reten-tion increases with simulation, while practice and repetition with spinal instrumentation placement improve accuracy and decrease pedicle breach by trainees. 14,15,19,[35][36][37] Repetition is also valuable beyond training environments, as experienced spine surgeons exhibit decreased rates of breach compared with lesser-experienced surgeons in nonnavigated pedicle screw placement in adolescent idiopathic scoliosis. 4 Computer-assisted navigation for pedicle screw placement improves accuracy of pedicle screw insertion and reduces the need for surgical revision.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Multiple studies have demonstrated that learning reten-tion increases with simulation, while practice and repetition with spinal instrumentation placement improve accuracy and decrease pedicle breach by trainees. 14,15,19,[35][36][37] Repetition is also valuable beyond training environments, as experienced spine surgeons exhibit decreased rates of breach compared with lesser-experienced surgeons in nonnavigated pedicle screw placement in adolescent idiopathic scoliosis. 4 Computer-assisted navigation for pedicle screw placement improves accuracy of pedicle screw insertion and reduces the need for surgical revision.…”
Section: Discussionmentioning
confidence: 99%
“…45 Therefore, adding this component to the model may improve trainee experience-based judgment. 37,38…”
Section: Future Studiesmentioning
confidence: 99%
“…This consists of task-oriented goals performed outside of the traditional operating room setting. Directed bioskills training improves trainee technical performance and decreases in-lab operating errors [137]. The most commonly used method of bioskills training is the utilization of human cadaveric models [138].…”
Section: Developments In Surgical Trainingmentioning
confidence: 99%
“…Bioskills training modules involving sawbone models were used to train both lumbar pedicle screw placement 84 and lumbar laminectomy 85 by the same group and assessed in a randomised trial. Both studies described the use of the OSATS, and the PPDIS and thus a rating 2 for response processes was achieved.…”
Section: Patel 18mentioning
confidence: 99%